Rancang Bangun Aplikasi Pemesanan SEMBAKO berbasis Mobile menggunakan Android - ; Zaki Imaduddin (LPPM STT Terpadu Nurul Fikri, 2017)
The staple foods of the community are often consumed both in groups and individually. By utilizing current technology, the authors designed an application to help the grocery sales process, starting from marketing goods, ordering goods, goods transactions, and receiving goods. The seller will also face challenges in service to his consumers due to the process in trading these essential food items, such as the time-consuming ordering process for one customer, the number of customers ordering at one time, providing goods to customers, calculating the costs to be paid, and delivery goods. Transactions that have been running so far still use COD (face to face) so that in the process, there are still calculation errors and fraud. The authors analyze and design applications with Waterfall software engineering methodology and use Unified Modeling Language (UML) modeling. The application design process is carrying out using the PHP programming language and MySQL as the database. The results of this design are expecting to solve the problems faced by the community.